(untitled) (Bangladesh Medical Journal Khulna, 2020)
Background: Urethrocutaneous fistula is the most prevalent complication after urethroplasty. Many methods have been developed for correction, and the best technique is determined based on the size, location, and number of fistulas, as well as the status of the surrounding skin. Objective: To compare the outcome of local dartos flap and tunnelled tunica vaginalis coverage in cases of repair of urethrocutaneous fistula. Materials and Methods: In the period of 2015-2018, 51 patients with 51 fistulas with an average age of 81.3 months (range 21-156 months) were classified into coronal-19, distal penile-11, mid penile-14, proximal penile-5 and penoscrotal-2. Thirty six patients were repaired with local dartos flap coverage and 15 patients were repaired with tunnelled tunica vaginalis coverage. Results: The repair was successful in all patients of tunica vaginalis coverage but 7 patients of dartos flap coverage developed recurrent fistulas (p value 0.066). There was no patient of scrotal complications. There were no statistically significant differences regarding age (p=0.83), location of fistula (p=0.40), size of fistula (p=0.29). Conclusions: Though the result of this study with such a small sample was not statistically significant, tunica vaginalis coverage seems to be better than dartos flap coverage in preventing recurrence. Bang Med J (Khulna) 2019; 52 : 3-6